Appendix: Part 4: General Inferences (Proceedings of the Society of Antiquaries of Scotland, 1866)
Chapter IX: Import of the Ring and Cup CuttingsChapter X: Their Alleged Phoenician OriginChapter XI: Their Probable Ornamental CharacterChapter XII: Their Possibly Religious CharacterChapter XIII: Question of their Age or DateChapter XIV: Their Precedence of Letters and TraditionsChapter XV: Their Connection with Archaic Towns and DwellingsChapter XVI: Their Presence on the Stones of the most Ancient Kinds of SepultureChapter XVII: The Archaic Character of the Contemporaneous Relics found in Combination with themChapter XVIII: The Kind of Tools Required for the SculpturingsChapter XIX: Their Antiquity, as shown by their Geographical Distribution in the British IslandsChapter XX: The Race that first Introduced the Lapidary Ring and Cup Sculpturings